LIVING A LIFE ONLINE: TRUST, EXPRESSION, AND INTERACTION IN MMOGS - Wirth, Richard; Guadagno, Rosanna (AoIR Selected Papers of Internet Research, 2015)
Life on the Internet has possibly as many forms and functions as real-world existence – a notion that is readily apparent through an examination of virtual worlds and Massively Multiplayer Online Games (MMOGs). In the daily operation of such a world, players face social interactions in much the same fashion that individuals are likely encounter in their offline “real” life (Guadagno, Muscanell, Okdie, Burk, and Ward, 2011). These gaming experiences are of course colored by both the nature of the medium and the unique design of the virtual world in question (Taylor, 1999, 2004; Park and Namho, 2011). Scholars seeking to study the medium itself often look to the ways in which video games affect behavior or facilitate the acquisition of social capital (Zhong, 2011; Collins & Freeman, 2013), while the analysis of specific virtual worlds is traditionally limited to the ethnographic study of social institutions, play communities, and the daily lives of players (Mnookin, 1996; Pearce 2009). This paper is the result of a literature review of social interaction and online communication, as well as a pilot study on MMOG players, examining the relationship between self-disclosure (Miller, Berg, & Archer, 1983), motivation (Yee, 2006), social perception, and resultant behavior. A small pilot study indicated that people’s motivations for gameplay as well as the group memberships of other players affect the likelihood of trusting and helping other players in MMOGs.